PHARMACOECONOMIC ANALYSIS OF VARIOUS BRANDS OF COMMONLY PRESCRIBED ORAL ANTIHYPERTENSIVE MEDICINES IN INDIAN MARKET - JHANWAR, ANSHUL (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objectives: The objective of the study was to analyze the percentage cost variations among various brands of the commonly prescribed antihypertensive medicines in India. Methods: Cost of a particular medicine (cost per 10 tablets) in the same strength and dosage forms being produced by various pharmaceutical companies was taken from Current Index of Medical specialties and Drug Today. Difference between the highest and lowest cost of the same drug manufactured by various pharmaceutical industries was obtained and percentage cost variation was calculated. Results: The percentage variation in the price was above 100% with almost all of the commonly prescribed antihypertensive medicines. The cost of a total of 23 drugs (14 single and nine combination preparations), available in forty nine different formulations were studied. Overall, Amlodipine (5 mg) shows highest price difference of 982.3%, while Nifedipine (5 mg) shows lowest price difference of 39%. Telmisartan + Hydrochlorthiazide (80+12.5 mg) combinations shows highest price variation of 318.9%, while Amlodipine + Losartan (5+50 mg) shows lowest price difference of 50%. Conclusion: The average percentage price difference of the same antihypertensive medicine manufactured by various pharmaceuticals company in India is very huge. Hence, Government, Pharmaceutical companies, prescribing health care workers should educate themselves about huge variation in price of brand drugs in comparison with their cheap generic counterpart to provide maximum benefits with minimum financial burden to the patients receiving antihypertensive drugs.